An analysis of case particles and case functions in Japanese: A case grammar approach - Suraiya Mohd. Ali (Journal of Modern Languages)
The paper focuses on an aspect of grammar, specifically, case particles or postpositions in Japanese. It is based on a discussion on case forms and case functions that are discoverable through an examination of the theory of case grammar by Fillmore (1968). The main objective of the paper is to raise consciousness among teachers as well as learners of Japanese through understanding and application of the Fillmorean case grammar. A conscious effort at equipping both teachers and learners with a firm knowledge of a universal grammar is felt to go a long way in making language teaching and learning more accurate and meaningful.